Alkali Metal and Alkaline Earth Metal Complexes with the Bis(borane‐diphenylphosphanyl)amido Ligand – Synthesis, Structures, and Catalysis for Ring‐Opening Polymerization of ϵ‐Caprolactone12. Issue 2 (27th November 2015) - Bhattacharjee, Jayeeta; Das, Suman; Reddy, T. Dhileep N.; Nayek, Hari Pada; Mallik, Bhabani S.; Panda, Tarun K.
Abstract: The syntheses of lithium and alkaline earth metal complexes with the bis(borane‐diphenylphosphanyl)amido ligand (1 ‐H ) of molecular formulas [ κ 2 ‐N(PPh2 (BH3 ))2 Li(THF)2 ] (2 ) and [κ 3 ‐N(PPh2 (BH3 ))2 2 M (THF)2 ] [( M = Ca (3 ), Sr (4 ), Ba (5 )] are reported. The lithium complex2 was obtained by treatment of bis(borane‐diphenylphosphanyl)amine (1 ‐H ) with lithium bis(trimethylsilyl)amide in a 1:1 molar ratio via the silylamine elimination method. The corresponding homoleptic alkaline earth metal complexes3 –5 were prepared by two synthetic routes – first, the treatment of metal bis(trimethylsilyl)amide and protio ligand1 ‐H via the elimination of silylamine, and second, through salt metathesis reaction involving respective metal diiodides and lithium salt2 . The molecular structures of lithium complex2 and barium complex5 were established by single‐crystal X‐ray diffraction analysis. In the solid‐state structure of2, the lithium ion is ligated by amido nitrogen atoms and hydrogen atoms of the BH3 group in κ 2 ‐coordination of the ligand1 resulting in a distorted tetrahedral geometry around the lithium ion. However, in complex5, κ 3 ‐coordination of the ligand1 was observed, and the barium ion adopted a distorted octahedral arrangement. The metal complex5 was tested as catalyst for the ring opening polymerization of ϵ‐caprolactone. High activity for the barium complex5 towards ring opening polymerization (ROP) of ϵ‐caprolactone with a narrow polydispersity index was observed. Additionally, first‐principle calculations to investigate the structure and coordination properties of alkaline earth metal complexes3 –5 as a comparative study between the experimental and theoretical findings were described. Abstract :